Äldre glesbygdskvinnor, bortglömda offer eller centralgestalter i lokalsamhället? - Liliequist, Marianne (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2009)
This study, based on participant observations and interviews, concerns the present situation of the elderly women in Frostviken, a sparsely populated mountain-area in the north of Sweden. What resources do these women have in order to achieve life-quality? Elderly women living in this part of the country is often described as victims in the periphery. In my study the elderly women have a central role in their community and in their network of relatives. They have high status because they stand out as symbols of the regional identity of Frostviken. The widows who choose to stay at the farms after their husbands have passed away, are resources to their families and relatives. The farm with all it’s assets — for example the built-up week-end cottages, the hunting- and fishing licences connected to the farm and the roots way back to the culture of the first settlers — is central to the ideal of life in Frostviken. As the owner of the farm the elderly women exist in the middle of a large network of relatives who come visiting from time to time. Her role as a story-teller with great knowledge of local- and family history further promotes her central position.